Quenching for a Non-Newtonian Filtration Equation with a Singular Boundary Condition - Xiliu Li; Chunlai Mu; Qingna Zhang; Shouming Zhou (Abstract and Applied Analysis)
This paper deals with a nonlinear p-Laplacian equation with singular boundary conditions. Under proper conditions, the solution of this equation quenches in finite time and the only quenching point thatis x=1 are obtained. Moreover, the quenching rate of this equation is established. Finally, we give an example of an application of our results.